Using respiratory polygraphy in diagnosing obstructive sleep apnea – our experiences - novković, dobrivoje; Cvetković, Gordana; Aćimović, Slobodan; Milić, Rade; Šarac, Sanja; Urošević, Radmila (Vojnosanitetski pregled, 2021)
Abstract Bacground/Aim. Obstructive sleep apnea (OSA) involves repeated episodes of cessation of breathing that occur due to a decrease in pharyngeal muscle tone. This disorder is more common in men and represents a significant risk factor for serious cardiovascular and cerebrovascular events. The gold standard in the diagnosis of this disorder represents a polysomnography (PSG), which is technically a complex and multidisciplinary method. Respiratory polygraphy (RP) may constitute an adequate replacement for most uncomplicated cases of obstructive sleep apnea. The aim of the study was to examine the efficacy of using respiratory polygraphies in diagnosing of obstructive sleep apnea. Methods. On all the patients with suspected obstructive sleep apnea, RP and a retrospective analysis of the obtained results were performed. Results. By completing our examination, we proved that there was a positive correlation between the results obtained by using RP and the predictors of obstructive sleep apnea such as the Epworth sleepiness scale (EPWORTH) score, neck circumference and body mass index. Conclusion. Respiratory polygraphy represents a cheaper and simpler replacement for PSG, especially with uncomplicated obstructive breathing disorders during sleep.
Keywords: sleep apnea syndrome; diagnostic techniques and procedures; respiratory function tests; risk factors